Prevalensi, Derajat Infeksi dan Sebaran Tungau Ayam pada Peternakan Ayam Petelur di Pulau Jawa - Hadi, Upik Kusumawati; Soviana, Susi; Khotimah, Husnul (Jurnal Veteriner, 2022)
Ectoparasite infestation is a problem that is often found in laying hens. Mites and chicken lice are ectoparasites that are spread in tropical countries and become a nuisance in chicken farms. The purpose of this study was to measure the prevalence and degree of infestation, and distribution of poultry mite in laying hens. This research was conducted in October-December 2018 in several areas of Java Island. The research areas include Kuningan and Bogor (West Java), Blitar and Kediri (East Java), and Purbalingga (Central Java). The study was conducted on 13 laying hens with a sample of 20 chickens in each farm. Chickens were taken directly from the cage and carried out a physical examination and observation of the presence of poultry mites. Kruskal-Wallis test was used to see the relationship between chicken body region and the number of each mite, as well as the effect of cage material on the degree of mite infestation. The results showed that all the farms studied were positively infested by poultry mites. The identification results showed that the types of mites that infested were Ornithonyssus bursa (positive on 3 farms) and Megninia ginglymura (positive on 13 farms). The highest mite population was in Farms 2 and 7 with an infestation prevalence of 100% in both farms. The thorax was the most common part of the body in O. bursa infestation, while M. ginglymura was most commonly found in the tail of poultry. It was concluded that there were two species of poultry mite infestations with different prevalence and degree of infestations on 13 commercial laying hens farms in Java Island.